2016
DOI: 10.1073/pnas.1524385113
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial Argonaute with noncanonical guide RNA specificity

Abstract: Eukaryotic Argonaute proteins induce gene silencing by small RNAguided recognition and cleavage of mRNA targets. Although structural similarities between human and prokaryotic Argonautes are consistent with shared mechanistic properties, sequence and structure-based alignments suggested that Argonautes encoded within CRISPR-cas [clustered regularly interspaced short palindromic repeats (CRISPR)-associated] bacterial immunity operons have divergent activities. We show here that the CRISPR-associated Marinitoga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
232
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(250 citation statements)
references
References 50 publications
8
232
2
4
Order By: Relevance
“…Previous biochemical experiments showed that MpAgo binds RNA guides and preferentially targets DNA [12]. Analysis of the MpAgo ternary complex crystallized in this study revealed that the bound RNA-DNA heteroduplex adopts a B-form-like helical geometry.…”
Section: Discussionmentioning
confidence: 63%
“…Previous biochemical experiments showed that MpAgo binds RNA guides and preferentially targets DNA [12]. Analysis of the MpAgo ternary complex crystallized in this study revealed that the bound RNA-DNA heteroduplex adopts a B-form-like helical geometry.…”
Section: Discussionmentioning
confidence: 63%
“…While RsAgo is inactive as an endonuclease and our attempts to restore its catalytic activity by point mutagenesis were unsuccessful (Figure S3), pAgos from other species have guide-dependent endonuclease activity both in vitro and in vivo (Kaya et al, 2016; Swarts et al, 2014a, 2015; Wang et al, 2008). In contrast to CRISPR/Cas9, pAgo-gRNA complex can potentially target virtually any sequence of interest as efficient recognition of the target does not require the presence of Protospacer adjacent motif (PAM), a short sequence following the DNA sequence targeted by Cas9.…”
Section: Discussionmentioning
confidence: 99%
“…While eukaryotic Agos use gRNAs to recognize and cleave target RNAs (Liu et al, 2004), pAgos were shown to use gRNAs (e.g., Rhodobacter sphaeroides RsAgo and MpAgo) or DNAs (e.g., TtAgo) to recognize target DNAs (tDNAs) (Kaya et al, 2016; Makarova et al, 2009; Olovnikov et al, 2013; Swarts et al, 2014a, 2014b; Yuan et al, 2005). Functional studies suggested that pAgos defend genomes against invasive DNA (Hur et al, 2014; Olovnikov et al, 2013; Schirle et al, 2014; Swarts et al, 2014a, 2015), a function similar to their eukaryotic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this idea, the crystal structure of T. thermophilus Argonaute revealed that the guide seed region is displayed in a pre-organized helical conformation [68]. Subsequent structures have found that pre-ordering of at least the 5′ end (g2–g5) of the seed is feature of all prokaryotic and eukaryotic Argonaute proteins studied thus far [64, 65, 67, 83, 141143]. Moreover, single molecule studies have demonstrated that Argonaute binds substantially faster and remains more stably associated to seed-paired target RNAs than an equivalent naked RNA duplex [6, 144].…”
Section: Argonaute Targeting Mechanismsmentioning
confidence: 91%